Quality of Vision after Deep Anterior Lamellar Keratoplasty (Fluid Dissection) Compared to Penetrating Keratoplasty for the Treatment of Keratoconus - Islam Mahmoud Hamdi; Momen Mahmoud Hamdi (Journal of Ophthalmology)
Purpose. To compare the visual quality of patients with keratoconus who underwent penetrating keratoplasty (PKP) or deep anterior lamellar keratoplasty (DALK) with fluid dissection. Design. Cross-sectional, observational study. Methods. Twelve eyes that underwent PKP (PKP group) were compared to 24 eyes that underwent DALK (DALK group) after complete removal of sutures and stability of refraction. Visual, refractive, corneal topographic, corneal aberrometry, and ocular aberrometry parameters were compared for both groups. The χ2 and Mann–Whitney U tests were used for comparisons as appropriate. P<0.05 was considered statistically significant. Results. Uncorrected and best spectacle-corrected visual acuity (UCVA and BSCVA, resp.), mean refractive spherical equivalent and mean refractive cylinder (MRSE and MRC, resp.), root mean square of the 3 mm and 5 mm OPD Scan (NIDEK Co. Ltd., Gamagori, Japan), steep and flat meridians (SimK1 and SimK2, resp.), and the difference (corneal cylinder) were not statistically significantly different between groups (P>0.05, all comparisons). All aberrations, point spread functions (PSF), and the modulation transfer function (MTF) were not statistically different between groups (P>0.05). Conclusion. For our small study, the postoperative PKP and DALK with fluid dissection patient groups had vision/optical quality parameters that were not statistically different. This may indicate that DALK with fluid dissection can replace PKP for keratoconus without compromising vision quality.